UTILIZING GREEN MARKETING TO ENHANCE AWARENESS AND UNIQUENESS IN USED COOKING OIL PROCESSING BUSINESSES - Salsabila Au'maylia Mutmainah; Berto Mulia Wibawa (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
Rising household consumption of cooking oil in Indonesia has increased the volume of used cooking oil waste, which poses environmental risks but also creates opportunities for circular-economy ventures. Dolmin, a business that collects used cooking oil and upcycles it into aromatherapy candles, still faces unstructured marketing efforts and consumer skepticism regarding the safety, cleanliness, and credibility of products derived from waste materials. This study develops a sustainability-based green marketing strategy to strengthen environmental education, brand identity, and economic value creation for Dolmin by integrating the Segmenting–Targeting–Positioning (STP) framework, Value Proposition Design (VPD), and the Business Model Canvas (BMC). Using a qualitative single- case study approach, data were gathered through in-depth interviews, participant observation, and documentation over the research period and analyzed thematically through the lens of STP, VPD, and BMC. The results propose a strategic positioning of Dolmin as an environmental education agent, emphasizing transparent communication from collection to processing and upcycling to reduce perceptions of greenwashing and build trust. The primary market segment is identified as women aged 25–40 with an interest in sustainable lifestyles, supported by secondary targets such as homemakers and business partners, and a value proposition combining sustainability, aesthetics, and social meaning. Practical recommendations include activating digital channels (Instagram and TikTok), strengthening storytelling, improving aesthetic product design, expanding variants and interactive features, and scaling partnerships with restaurants, schools, communities, and influencers. Overall, the integrated strategy offers an implementable business development roadmap and provides practical insights for similar waste-management enterprises promoting responsible consumption and production.